Sum Rate Optimization by Spatial Precoding for a Multiuser MIMO DFT-Precoded OFDM Uplink. (7th March 2011) - Wu Wu, Hanguang Hanguang; Haustein Haustein, Thomas Thomas; Jorswieck Jorswieck, Eduard Axel Eduard Axel; Hoeher Hoeher, Peter Adam Peter Adam
Abstract : By means of DFT-precoding, the PAPR of OFDM waveforms can be reduced. DFT-precoding has been proposed for uplink transmission in various future wireless communication systems. In this work, we consider DFT-precoding combined with spatial precoding for the uplink of multiuser MIMO OFDM systems. An efficient algorithm is developed to optimize the spatial precoder aiming at maximization of the system sum rate subject to individual power constraints of the users and maintenance of the low PAPR property for one user. Potential gains are shown compared to other popular precoding methods in 3GPP-LTE uplink scenarios.